Short-term choroidal thickness changes in patients treated with either ranibizumab or aflibercept: a comparative study - Kim, Jae Hui; Lee, Tae Gon; Chang, Young Suk; Kim, Chul Gu; Cho, Sung Won (British journal of ophthalmology, 2016)
PurposeTo compare, in neovascular age-related macular degeneration (AMD) patients, short-term choroidal thickness changes in eyes treated using ranibizumab with those in eyes treated using aflibercept.MethodsThis retrospective, observational study included 240 eyes from 240 patients who had been diagnosed with treatment-naive neovascular AMD and treated using three monthly injections of either ranibizumab (ranibizumab group) or aflibercept (aflibercept group). The choroidal thickness change between the time of diagnosis and 3 months later was compared between the two groups. Eyes were then classified into three disease groups: typical neovascular AMD, polypoidal choroidal vasculopathy (PCV) and retinal angiomatous proliferation (RAP). Within each disease group, choroidal thickness change was again compared between the two treatment groups.ResultsIn the ranibizumab group (n=155), the mean choroidal thicknesses at diagnosis and at 3 months were 255.3±103.9 μm and 242.9±104.8 μm, respectively. In the aflibercept group (n=85), the values were 277.5±119.1 μm and 254.7±114.5 μm, respectively. The decrease was significantly greater in the aflibercept group (p<0.001). In the PCV group, the decrease was greater in the aflibercept group (p=0.001), whereas the difference was not significant in either the typical neovascular AMD group or the RAP group.ConclusionsA greater decrease in choroidal thickness was noted in eyes treated with aflibercept than in eyes treated with ranibizumab. This difference was more marked in PCV than in other subtypes of neovascular AMD.